Peritonitis-related bacterial infections: a large-scale case-series retrospective study in 160 domestic animals (2009–2022) - Ribeiro, Márcio Garcia [UNESP]; da Silva Ribeiro, Ana Beatriz [UNESP]; da Silva, Ana Beatriz Matias [UNESP]; Mariano, Gabriel Henrique Gomes [UNESP]; de Sá Teles Bertunes, Larissa [UNESP]; Portilho, Fábio Vinicius Ramos [UNESP]; Filho, Marcelo Fagali Arabe [UNESP]; Bello, Thaís Spessotto [UNESP]; Meira, Júlia [UNESP]; de Lima Paz, Patrik Júnior [UNESP]; Siqueira, Amanda Keller; Motta, Rodrigo Garcia; et al. (Springer Nature, 2024)
Bacterial peritonitis infections comprise a life-threatening clinical condition in domestic animals that commonly lead to sepsis and high mortality. A set of bacterial pathogens have been identified in septic peritonitis in livestock and companion animals. Nonetheless, most descriptions are restricted to case reports or limited to only one domestic species, and a restrict number of comprehensive studies involving this infection has focused on a great number of domestic animals. Here, we retrospectively investigated selected epidemiological data (with an emphasis in outcome), clinical signs, bacteriological culturing, and in vitro antimicrobial susceptibility patterns of microorganisms isolated of peritoneal fluid from 160 domestic animals (2009–2023) compatible with septic peritonitis. Bacteria were isolated from 71.9% (115/160) of the peritoneal fluid from 75 dogs (75/115 = 65.2%), 22 cats (22/115 = 19.1%), 14 horses (14/115 = 12.2%), and 4 cattle (4/115 = 3.5%). Among animals with bacterial isolation, Escherichia coli (34/115 = 29.6%), alfa-hemolytic Streptococcus (12/115 = 10.4%), Staphylococcus aureus (8/115 = 6.9%), beta-hemolytic Streptococcus (7/115 = 6.1%), and Pasteurella multocida (6/115 = 5.2%) were predominant in pure culture, in addition to a miscellaneous of other bacteria isolated in minor frequency, e.g., Pseudomonas sp., Trueperella pyogenes, Klebsiella pneumoniae, and Salmonella sp. In general, in vitro susceptibility tests of isolates revealed that florfenicol, chloramphenicol, and amoxicillin/clavulanic acid showed moderate effectivity (≥ 60%). Conversely, most of isolates exhibited resistance mainly to trimethoprim/sulfamethoxazole, enrofloxacin, and penicillin (> 60%). Additionally, multidrug resistance was found in 42.6% (49/115) of the isolates. Data related to the outcome were available in 37.4% (43/115) of animals that had bacterial isolation and, from these, the mortality rate was 79.1% (34/43), with a significant association (p < 0.036) between mortality and septic peritonitis by gram-negative bacteria. Neoplasia (7/43 = 16.3%), pneumonia/pulmonary abscess (5/43 = 11.6%), hepatitis (5/43 = 11.6%), metritis/pyometra (4/43 = 9.3%), and gall bladder rupture (3/43 = 7%) represented the probable main sources of septic peritonitis. Anorexia (34/115 = 29.6%), emesis (29/115 = 25.2%), lethargy (26/115 = 22.6%), respiratory distress (25/115 = 21.7%), ascites (20/115 = 17.4%), and fever (19/115 = 16.5%) were the most frequent clinical signs among animals with bacterial isolation. A variety of bacteria were isolated in the peritoneal fluid of animals, with a predominance of Enterobacteriaceae, streptococci, and staphylococci, highlighting the opportunistic nature of the pathogens in septic peritonitis. High in vitro multidrug resistance of isolates and high mortality of animals reinforce the need for early diagnosis and therapy based on the in vitro antimicrobial profile of the pathogens involved in septic peritonitis. Our results contribute to the etiological characterization, clinical-epidemiological findings, and vigilance of multidrug-resistant bacteria in septic peritonitis among livestock and companion animals.
Keywords: Companion animals; Etiology; Livestock; Multidrug-resistant bacteria; Outcome; Peritoneal infections